Teacher readiness and challenges in creating learner autonomy in ICT-based English learning activities - Syafryadin, Syafryadin; Suherdi, Didi; Nadya, Nyayu Lulu; Harahap, Alamsyah; Astrid, Annisa (Indonesian Journal of Applied Linguistics, 2022)
The significance of learner autonomy in today’s English Language Teaching (ELT) context has been well recognized and confirmed by many research findings; however, in some cases in which independent learning is not well established, the implementation may not be easy. Thus, this research is intended to provide data on teachers’ readiness and challenges in promoting learner autonomy during online learning activities. This research employed quantitative and qualitative data collection. The quantitative data were gained by a survey that has been conducted to 38 English teachers in 38 junior high schools in Bengkulu. In addition, the qualitative data were collected from an interview that has also been carried out to six teachers. The quantitative data obtained were then analysed through descriptive statistics analysis in the form of percentages and frequency. Meanwhile, the qualitative data were analysed by using thematic analysis. The results showed that in general most teachers were ready to build learner autonomy in ICT-based English learning. Most teachers used various methods in online teaching, gave freedom for the students to access different online resources according to their interest, found it easy to carry out online learning, yet most of them did not prefer to implement online learning activities. In the implementation, some challenges were faced by teachers, including poor internet connection, students’ different characteristics, and lack support from school policymakers.